Late diagnosis of HIV in 2022: Why so little change?. Issue 11 (17th November 2022) - Collins, Simon; Namiba, Angelina; Sparrowhawk, Alex; Strachan, Sophie; Thompson, Marc; Nakamura, Hideta
Abstract: Background: The proportion of people who are diagnosed late is a key metric to measure the public health response to HIV. But this percentage remains stubbornly high in nearly every country. Delays in accessing antiretroviral therapy affects both (i) individual health, due to a higher risk of mortality, and (ii) population‐based health, due to continued risk of transmission. Despite huge efforts to increase testing, late diagnosis continues to be an indication of a public health failure. Outline: This short review includes community perspectives on why late diagnosis continues and how it may be reduced. We discuss both structural barriers that prevent people from testing earlier and personal reasons why some people still refuse testing when offered. We note that late diagnosis is reported in all countries and in all demographic groups and that sex, gender, age, and sexuality all affect these rates. However, even in groups with high HIV awareness, such as in gay and bisexual men in the UK, more than one in three people with HIV continue to be diagnosed late. Fears and prejudice about HIV based on outdated information are still common among both health workers and people using health services. For example, testing is still not offered in primary or emergency care settings, and even free testing might not be accepted if someone fears the outcome might jeopardize their resident status, employment, relationship, or health. Summary: In addition to developing targeted projects to reach the highest‐risk groups, a positive mainstream public campaign could make testing more acceptable at a broad population level across all demographics. This could challenge and repair the media campaigns from the 1980s that still contribute to the stigma that frightens people away from testing now. We hope that an effective approach in one country might also help others.